Komunikasi Dialogis Sebagai Upaya Penyadaran Kritis Dalam Rangka Transformasi Pendidikan Modern - Fariz Luthfi Priyono (Ilmu Komunikasi, 2026)
Abstract - This article critically examines dialogic communication as a fundamental mechanism for fostering critical consciousness in the transformation of modern education. Contemporary education systems are increasingly dominated by instrumental rationality, standardization, and outcome-oriented learning, which often marginalize reflective dialogue and critical engagement of learners. This study aims to conceptualize dialogic communication as a transformative communication practice that enables learners to become reflective, critical, and socially conscious subjects. Using a conceptual qualitative approach supported by an extensive literature review of contemporary critical communication theory and pedagogy, this study analyzes dialogic communication through the perspectives of Paulo Freire, Jürgen Habermas, Henry Giroux, and bell hooks. The findings indicate that dialogic communication functions not only as a pedagogical technique but also as an epistemological and ethical foundation for emancipatory education. Dialogic practices encourage reciprocal shared meaning-making, critical reflection on social reality, and democratic participation in the learning process. This article argues that dialogic communication is crucial for transforming modern education into a humanistic and emancipatory system capable of producing critically conscious citizens. This research makes theoretical contributions to the discourse on communication and education, and offers practical implications for educators and policymakers who are working towards sustainable educational transformation.